Evolution of Somite Compartmentalization: A View From Xenopus - Della Gaspera, Bruno; Weill, Laure; Chanoine, Christophe (Frontiers in Cell and Developmental Biology, 2022)
Somites are transitory metameric structures at the basis of the axial organization of vertebrate musculoskeletal system. During evolution, somites appear in the chordate phylum and compartmentalize mainly into the dermomyotome, the myotome, and the sclerotome in vertebrates. In this review, we summarized the existing literature about somite compartmentalization in Xenopus and compared it with other anamniote and amniote vertebrates. We also present and discuss a model that describes the evolutionary history of somite compartmentalization from ancestral chordates to amniote vertebrates. We propose that the ancestral organization of chordate somite, subdivided into a lateral compartment of multipotent somitic cells (MSCs) and a medial primitive myotome, evolves through two major transitions. From ancestral chordates to vertebrates, the cell potency of MSCs may have evolved and gave rise to all new vertebrate compartments, i.e., the dermomyome, its hypaxial region, and the sclerotome. From anamniote to amniote vertebrates, the lateral MSC territory may expand to the whole somite at the expense of primitive myotome and may probably facilitate sclerotome formation. We propose that successive modifications of the cell potency of some type of embryonic progenitors could be one of major processes of the vertebrate evolution.